The influence of excessive body weight on the parameters of circadian hemodynamic rhythms (Experimental biology, 2018)
In terms of the attributable number of deaths, the main risk factor for non-communicable diseases globally is hypertension, obesity and obesity follow it in importance. In this study we studied the influence of body mass index indices on the circadian rhythms of the basic parameters of the hemodynamics. Practically healthy volunteer students of both sexes (N = 78), aged 17 to 27, with an average age of 20.7 ± 2.78 years, predominantly Kazakh ethnicity (97%) took part in the studies. Students with normal body mass index (BMI) in this age group are about 66% of the studied population, also we identified students with insufficient body weight (deficiency), with a body mass index in the range 16-18.5, their percentage was 12.3% of this sample. The percentage of students with overweight was 20%, obese students were 1.54% of this sample. According 7-days ABPM data the mean values ​​of MESORs in overweight female students are higher, but do not have statistically significant differences comparing with normal weight students, vascular variability anomalies (Circadian Hyper_Amplitude_Tension (CHAT), ecphasia) also do not correlate with BMI in young women. However, young men have positive positive correlations between hemodynamic parameters (SBP,  DBP and DP) and body mass index.Key words: overweight, chronostructure, ambulatory blood pressure monitoring, young people